A sustainable collaborative approach to the distribution network design problem with CO2 emissions allocation. (26th January 2022) - Mrabti, Nassim; Hamani, Nadia; Delahoche, Laurent
Horizontal collaboration is one of the best strategies used to improve freight transportation performance in terms of sustainability. In this paper, we address the collaborative distribution network design problem by reducing CO2 emissions. Contrary to most studies, we do not limit our research to the evaluation of CO2 emissions caused by transport, but we also evaluate the CO2 emissions caused by vehicle depreciation and those generated by hubs due to their operation and construction. To demonstrate the pooling performance, three scenarios are considered. The first one is a non-collaborative scenario where suppliers are independent of each other in transport and storage, while the second one is a collaborative scenario without addressing the vehicle routing problem in the downstream part of the network. This problem is considered in the third scenario. The performance of the collaboration is evaluated by a case study of a French distribution network. Moreover, we address the CO2 emissions allocation problem between partners by using three allocation approaches, namely average, volume and Shapley value. Relevant results are obtained by the collaborative networks with a significant reduction of the negative impact of each partner on the environment.